2014
DOI: 10.3109/00016357.2014.982704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lidocaine patches on upper trapezius EMG activity and pain intensity in patients with myofascial trigger points: A randomized clinical study

Abstract: These clinical and EMG results support the use of 5% lidocaine patches for treating patients with MTrP of the upper trapezius muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The most commonly used drugs include nonsteroidal anti-inflammatory drugs (NSAIDs), corticoids, analgesics, muscle relaxants, anxiolytics, opiates, tricyclic antidepressants (TCAs), gabapentin, and lidocaine patches. 57 60 Some of these medications are used to treat the joint pain of the TMD, and others are more effective for treating muscle pain.…”
Section: Oral and Topical Pharmacotherapymentioning
confidence: 99%
“…The most commonly used drugs include nonsteroidal anti-inflammatory drugs (NSAIDs), corticoids, analgesics, muscle relaxants, anxiolytics, opiates, tricyclic antidepressants (TCAs), gabapentin, and lidocaine patches. 57 60 Some of these medications are used to treat the joint pain of the TMD, and others are more effective for treating muscle pain.…”
Section: Oral and Topical Pharmacotherapymentioning
confidence: 99%
“…Bouchard et al [28] and Vos et al [29] reported a lack of evidence to support arthrocentesis as a better ther-apeutic intervention than nonsurgical interventions. Furthermore, they underlined the prominent role of conservative treatments such as physical therapy and oral/topical and injected pharmacotherapies and suggested their superiority over surgery, since they are less invasive and usually produce satisfying clinical results in mild-moderate TMD [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies on treatment efficacy have been conducted that measure the PPT at the TrP site before and after an intervention. Among these are dry needling [ 22 , 23 ], botulinum toxin [ 24 ], ischemic compression therapy [ 25 , 26 ], Kinesio taping [ 27 ], as well as lidocaine patches [ 28 ], exercises, and massage [ 29 ]. Although any of these treatments may be claimed to be effective in managing TrPs, a normative value of a clinically meaningful amount of pre-post difference in the PPT following whatever intervention has not been established yet.…”
Section: Introductionmentioning
confidence: 99%